2022
DOI: 10.7759/cureus.27408
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine-Induced Myocarditis: A Systemic Review and Literature Search

Abstract: Myocarditis is one of the complications reported with COVID-19 vaccines, particularly both Pfizer-BioNTech and Moderna vaccines. Most of the published data about this association come from case reports and series. Integrating the geographical data, clinical manifestations, and outcomes is therefore important in patients with myocarditis to better understand the disease. A thorough literature search was conducted in Cochrane library, PubMed, ScienceDirect, and Google Scholar for published literature till 30 Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
(41 reference statements)
1
7
0
Order By: Relevance
“…Although several case studies have reported clinical changes in BNT162b2-MyoC patients, our understanding of BNT162b2-MyoC is still limited mainly due to scarcity of tissue sampling and lack of empirical evidence ( 45 ). Moreover, based on published literature reviews ( 46 , 47 ), among few empirical studies that were conducted with tissue samples from patients, there hasn’t been research that featured detailed transcriptomic profile of the harvested tissues. Myocarditis is a local inflammation of the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Although several case studies have reported clinical changes in BNT162b2-MyoC patients, our understanding of BNT162b2-MyoC is still limited mainly due to scarcity of tissue sampling and lack of empirical evidence ( 45 ). Moreover, based on published literature reviews ( 46 , 47 ), among few empirical studies that were conducted with tissue samples from patients, there hasn’t been research that featured detailed transcriptomic profile of the harvested tissues. Myocarditis is a local inflammation of the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Pericarditis is a somewhat prevalent cause of chest pain, and around 5% of all hospitalizations for chest pain are due to pericarditis 119 . Myocarditis has been reported as a major side effect of these vaccines; however, the overall rate of post-COVID19 vaccination-myocarditis is around 1.62% which is very small 120 , 121 , 122 .…”
Section: Resultsmentioning
confidence: 99%
“…A recent systematic review on myocarditis after COVID-19 vaccination reported only one case after Astra Zeneca, one case after Sputnik V injection, and one case after vector Johnson & Johnson, out of a total of 277 cases 120 . A 32-year-old female case developed myocarditis on the third day after receiving the first dose of the AstraZeneca.…”
Section: Resultsmentioning
confidence: 99%
“…In this condition, cardiac enzymes, electrocardiography (ECG), and echocardiography are mandated, and if indicated, a CMR can also be performed (Figure 3). Notably, a systematic review of the COVID-19 vaccineinduced myocarditis showed that all patients underwent CMR, and CMR finding related to the myocarditis was evident in 89% of patients [65]. One must be careful not to immediately attribute all cardiac events to the vaccine, and other etiologies must be excluded [64].…”
Section: Covid-19 Vaccine-associated Myocarditismentioning
confidence: 99%
“…Regardless of its etiology, NSAIDs, steroids, intravenous immunoglobulin, and colchicine are treatment options for myocarditis. It was shown that NSAIDs, colchicine, and steroids are the most frequent medications used to manage COVID-19 vaccine-induced myocarditis [65]. Regarding COVID-19 vaccine-induced myocarditis in pediatrics, NSAIDs were recommended as a first-line treatment option.…”
Section: Covid-19 Vaccine-associated Myocarditismentioning
confidence: 99%